Preclinical Investigation of Alpinetin in the Treatment of Cancer-Induced Cachexia via Activating PPARγ - Zhang, Yujie; Zhang, Yuxin; Li, Yichen; Zhang, Li; Yu, Shiying (Frontiers in Pharmacology, 2021)
The ongoing loss of skeletal muscle is a central event of cancer cachexia, and its consequences include adverse effects on patient’s quality of life and survival. Alpinetin (Alp), a natural plant-derived flavonoid obtained from Alpinia katsumadai Hayata, has been reported to possess potent anti-inflammatory and antitumor activities. This study aimed to explore the therapeutic effect and underlying mechanism of Alp in the prevention of cancer cachexia. We found that Alp (25–100 μM) dose-dependently attenuated Lewis lung carcinoma–conditioned medium-induced C2C12 myotube atrophy and reduced expression of the E3 ligases Atrogin-1 and MuRF1. Moreover, Alp administration markedly improved vital features of cancer cachexia in vivo with visible reduction of the loss of tumor-free body weight and wasting of multiple tissues, including skeletal muscle, epididymal fat, and decreased expression of Atrogin-1 and MuRF1 in cachectic muscle. Alp suppressed the elevated spleen weight and serum concentrations of tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, and IL-6. Further, Alp treatment remained protective against cancer cachexia in the advanced stage of tumor growth. Molecular docking results suggested that Alp was docked into the active site of PPARγ with the docking score of –7.6 kcal/mol, forming a hydrogen bond interaction with PPARγ protein amino acid residue HIS449 with a bond length of 3.3 Å. Mechanism analysis revealed that Alp activated PPARγ, resulting in the downregulated phosphorylation of NF-κB and STAT3 in vitro and in vivo. PPARγ inhibition induced by GW9662 notably attenuated the improvement of Alp on the above cachexia phenomenon, indicating that PPARγ activation mediated the therapeutic effect of Alp. These findings suggested that Alp might be a potential therapeutic candidate against cancer cachexia.